2018
DOI: 10.1039/c8qo00591e
|View full text |Cite
|
Sign up to set email alerts
|

One-pot transition-metal free transamidation to sterically hindered amides

Abstract: A highly efficient one-pot transamidation of primary amides has been developed under transition-metal free conditions, generating a variety of amides including hindered amides in good yield (up to 86%) catalyzed by CsF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…Based on the control experiments, our previous reports and N ‐acyl‐tert‐butyl‐carbamates favoring ground‐state destabilization, we hypothesized that the first step is a transamidation . Amide 1 a was attacked by nucleophilic o ‐bromoaniline to form corresponding transamidation product 4 a with the regeneration of the CsF catalyst under base‐free conditions; then, the second step is a transition‐metal catalyzed cyclization, which is known in the Cu‐catalyzed C−X bond transformation literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the control experiments, our previous reports and N ‐acyl‐tert‐butyl‐carbamates favoring ground‐state destabilization, we hypothesized that the first step is a transamidation . Amide 1 a was attacked by nucleophilic o ‐bromoaniline to form corresponding transamidation product 4 a with the regeneration of the CsF catalyst under base‐free conditions; then, the second step is a transition‐metal catalyzed cyclization, which is known in the Cu‐catalyzed C−X bond transformation literature.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has already reported that CsF can react with amide bonds to form the corresponding acyl fluorides by site‐selective C−N bond cleavage, as mentioned above . Thus, we hypothesized that this in situ‐ generated acyl fluoride could be utilized in the synthesis of benzoxazoles (Scheme c).…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, they reported an impressive one-pot, transition-metal-free transami-dation of primary amides via a cesium fluoride catalyzed pathway (Scheme 27). 54 In this protocol, the primary amide is first converted via site-selective N-tert-butoxycarbonylation into twisted N,N-Boc 2 -amides (see also Scheme 19), followed by CsF-catalyzed transamidation to form the amide products in excellent yields. Notably, the method is compatible with various functional groups and steric hindrance owing to the mild conditions for amide formation.…”
Section: Tandem Transamidationsmentioning
confidence: 99%
“…Zeng and co-workers developed a one-pot activation of amide by its transformation to a sterically hindered tertbutyl dicarbonate (Scheme 23), that induced a twisting of the amide (see Scheme 1, B). 54 Scheme 23 One-pot transamidation to sterically hindered amides 54 Cesium fluoride was employed as catalyst for the in situ transformation of Boc-activated amide 136 to the corresponding acyl fluoride 138, which can be trapped by a variety of amines (Scheme 23). The conditions are mild, with high functional group and steric tolerance.…”
Section: Special Topic Synthesismentioning
confidence: 99%